2019
DOI: 10.1503/jpn.170242
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal, epigenome-wide study of DNA methylation in anorexia nervosa: results in actively ill, partially weight-restored, long-term remitted and non-eating-disordered women

Abstract: Background:This study explored state-related tendencies in DNA methylation in people with anorexia nervosa. Methods: We measured genome-wide DNA methylation in 75 women with active anorexia nervosa (active), 31 women showing stable remission of anorexia nervosa (remitted) and 41 women with no eating disorder (NED). We also obtained postintervention methylation data from 52 of the women from the active group. Results: Comparisons between members of the active and NED groups showed 58 differentially methylated s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 54 publications
2
29
0
Order By: Relevance
“…While the family in which ESRRA R188Q mutation was found has a high rate of AN and comorbidity of obsessive-compulsive disorder (OCD), another family in which HDAC4 A786T mutation was found has higher rates of BN but significantly lower rates of comorbid OCD. Multiple independent studies have shown that many CpG sites located in genomic region around 5 upstream of HDAC4 gene are differentially methylated in the peripheral tissues of patients with AN (Booij et al, 2015;Kesselmeier et al, 2018;Subramanian et al, 2018;Sild and Booij, 2019;Steiger et al, 2019), further supporting the role of HDAC4 in the pathophysiology of EDs. In the followup mouse studies, we found that Esrra knockout mice display behavioral deficits relevant to EDs, including reduced food intake, decreased motivation to work for high-fat diet (HFD), and social subordination (Cui et al, 2015).…”
Section: Introductionmentioning
confidence: 84%
“…While the family in which ESRRA R188Q mutation was found has a high rate of AN and comorbidity of obsessive-compulsive disorder (OCD), another family in which HDAC4 A786T mutation was found has higher rates of BN but significantly lower rates of comorbid OCD. Multiple independent studies have shown that many CpG sites located in genomic region around 5 upstream of HDAC4 gene are differentially methylated in the peripheral tissues of patients with AN (Booij et al, 2015;Kesselmeier et al, 2018;Subramanian et al, 2018;Sild and Booij, 2019;Steiger et al, 2019), further supporting the role of HDAC4 in the pathophysiology of EDs. In the followup mouse studies, we found that Esrra knockout mice display behavioral deficits relevant to EDs, including reduced food intake, decreased motivation to work for high-fat diet (HFD), and social subordination (Cui et al, 2015).…”
Section: Introductionmentioning
confidence: 84%
“…Although the studies in question are heterogenous with respect to methodology and results [ 18 ▪ , 23 ], available findings point to the potentials of epigenetic processes to constitute molecular mechanisms that could link environmental impacts, experienced at various moments throughout the life cycle (perinatal, childhood and adult) to mental-health outcomes, including eating disorders [ 8 , 18 ▪ , 23 ]. Importantly, methylation of some genes can also be altered by psychotherapeutic, nutritional or pharmacologic interventions [ 25 , 26 ▪▪ ], which raises the promise that changes in DNA methylation could serve as a marker for disease risk, staging, prognosis or therapeutic response.…”
Section: What Is Dna Methylation?mentioning
confidence: 99%
“…To date, three studies have conducted epigenome-wide analyses in individuals with eating disorders [ 26 ▪▪ , 30 , 31 ], all three involving anorexia nervosa. The most recent of these [ 26 ▪▪ ] compared epigenome-wide DNA methylation patterns in leukocytes of 75 individuals with anorexia nervosa, 31 in remission from anorexia nervosa for at least 1 year, and 41 normal-weight healthy eaters [ 26 ▪▪ ]. It also assessed DNA methylation after 4 months of standardized treatment for anorexia nervosa.…”
Section: Epigenome-wide Methylation Studies In Eating Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on candidate genes examined the serotonergic system (5-HT system), dopaminergic system, and opioidergic system that affect appetite, reward mechanism, mood, and weight; nevertheless, statistically significant results have not been presented so far [51]. Genome wide studies showed a relation between chromosomes 1, 11, and 12 and genes related to leptin regulation, lipid and glucose metabolism, serotonin receptor activities, and the immune system [52][53][54][55]. This genetic presentation is also consistent with the clinical presentation of anorexia.…”
Section: Genetic Explanationsmentioning
confidence: 99%